Tax Reforms, 'Free Lunches', and 'Cheap Lunches' in Open Economies - Tervala, Juha.; Ganelli, Giovanni (Washington, D.C. : International Monetary Fund, 2008)
This paper focuses on the macroeconomic and budgetary impact of tax reforms in a New Keynesian two-country model. Our results show that both income and consumption unilateral tax rate reductions do not constitute a "free lunch", in the sense that they have negative budgetary consequences for the country which implements them. In addition, the degree of self-financing implied by our model is in the 8 1\2 -24 percent range. Since the degree of self-financing estimated in previous literature was larger, we conclude that in our model not only the "lunch" is not "free", but is also not that "cheap". A comparison of alternative (income-tax versus consumption-tax based) fiscal stimulus packages shows that consumption tax cuts imply a larger short-run impact on domestic output but the income tax cuts stimulate the domestic economy more in the long run. We also look at the implications of a revenue-neutral tax reform in which consumption taxes are increased to compensate for lower income tax collection.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet